Role of COVID-19 Vaccines in SARS-CoV-2 Variants - Zhou, Zhou; Zhu, Yimiao; Chu, Ming (Frontiers in Immunology, 2022)
Coronavirus disease 19 (COVID-19), caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), is a threat to the health of the global population. As a result of the global efforts in the determination of origin, structure, and pathogenesis of SARS-CoV-2 and its variants, particularly the variants of concern such as Delta Variant and Omicron Variant. The progress in enhancing a sound knowledge of SARS-CoV-2 has been ongoing. Unfortunately, vaccines are unable to get completely effective against the virus, whether AstraZeneca-Vaxzevria/SII-Covishield vaccine, Janssen-Ad26.COV2.S vaccine, Moderna-mRNA-1273 vaccine, Pfizer BioNTech-Comirnaty vaccine and Sinovac-CoronaVac vaccine. Since the antigen escape caused by the mutation in variants, the effectiveness of vaccines, which are the current main means of prevention and treatment, has been affected by varying degrees. Herein, we review the current status of mutations of the SARS-CoV-2 variants, the different approaches used in the development of COVID-19 vaccines, and COVID-19 vaccine effectiveness against SARS-CoV-2 variants.